Dietary Docosahexaenoic Acid Prevents Silica-Induced Development of Pulmonary Ectopic Germinal Centers and Glomerulonephritis in the Lupus-Prone NZBWF1 Mouse - Bates, Melissa A.; Akbari, Peyman; Gilley, Kristen N.; Wagner, James G.; Li, Ning; Kopec, Anna K.; Wierenga, Kathryn A.; Jackson-Humbles, Daven; Brandenberger, Christina; Holian, Andrij; Benninghoff, Abby D.; Harkema, Jack R.; et al. (Frontiers in Immunology, 2018)
Ectopic lymphoid structures (ELS) consist of B-cell and T-cell aggregates that are initiated de novo in inflamed tissues outside of secondary lymphoid organs. When organized within follicular dendritic cell (FDC) networks, ELS contain functional germinal centers that can yield autoantibody-secreting plasma cells and promote autoimmune disease. Intranasal instillation of lupus-prone mice with crystalline silica (cSiO2), a respirable particle linked to human lupus, triggers ELS formation in the lung, systemic autoantibodies, and early onset of glomerulonephritis. Here we tested the hypothesis that consumption of docosahexaenoic acid (DHA), an ω-3 polyunsaturated fatty acid with anti-inflammatory properties, influences the temporal profile of cSiO2-induced pulmonary ectopic germinal center formation and development of glomerulonephritis. Female NZBWF1 mice (6-wk old) were fed purified isocaloric diets supplemented with 0, 4, or 10 g/kg DHA - calorically equivalent to 0, 2, or 5 g DHA per day consumption by humans, respectively. Beginning at age 8 wk, mice were intranasally instilled with 1 mg cSiO2, or saline vehicle alone, once per wk, for 4 wk. Cohorts were sacrificed 1, 5, 9, or 13 wk post-instillation (PI) of the last cSiO2 dose, and lung and kidney lesions were investigated by histopathology. Tissue fatty acid analyses confirmed uniform dose-dependent DHA incorporation across all cohorts. As early as 1 wk PI, inflammation comprising of B (CD45R+) and T (CD3+) cell accumulation was observed in lungs of cSiO2-treated mice compared to vehicle controls; these responses intensified over time. Marked follicular dendritic cell (FDC; CD21+/CD35+) networking appeared at 9 and 13 wk PI. IgG+ plasma cells suggestive of mature germinal centers were evident at 13 wk. DHA supplementation dramatically suppressed cSiO2-triggered B-cell, T-cell, FDC, and IgG+ plasma cell appearance in the lungs as well as anti-dsDNA IgG in bronchial lavage fluid and plasma over the course of the experiment. cSiO2 induced glomerulonephritis with concomitant B-cell accumulation in the renal cortex at 13 wk PI but this response was abrogated by DHA feeding. Taken together, realistic dietary DHA supplementation prevented initiation and/or progression of ectopic lymphoid neogenesis, germinal center development, systemic autoantibody elevation, and resultant glomerulonephritis in this unique preclinical model of environment-triggered lupus.